Vers un dispositif innovant de formation à la communication des médecins généralistes avec leurs patients : une démarche didactique professionnelle pour identifier des ajustements multiregistres - Andry Rabiaza; Eric Saillot (Questions Vives)
This article presents an exploratory approach of a PhD research which aim to build an innovative program to educate the general practitioners (GPs) to better communicate with their patients. The research is based on the multi-class adjustments model and a professional didactics process. The first steps have looked to identify the GPs’ representations about their adjustments in their communication with their patients. The second step has experimented an innovative training program based on self-confrontation interviews to analyse the communication and relation competencies in development among GPs inside a patient-centered approach.